The Effect of Audit Committee Characteristics and Board Size Moderated by Ownership Concentration on Profitability of Commercial Banks in Indonesia - Maulana, Tubagus Rama; Usman, Bahtiar; Nalurita, Febria (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the effect of audit committee size, audit committee independence, audit committee meetings, board size, bank size, leverage on profitability with variable ownership concentration as a moderating variable in banking companies in Indonesia. Profitability in this study is focused on assessing the company's ability to generate corporate profits against company assets (ROA). Sample selection using purposive sampling method in this study was conducted on 41 conventional commercial bank companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 - 2023. The data used in this study are secondary data sourced from the annual reports of banking companies published on the Indonesia Stock Exchange. Data analysis using multiple regression tests, using Eviews 10 in data processing. The results of this study are audit commitee size has an insignificant effect on profitability. In model 1 audit commitee independence has a negative and significant effect on profitability. In model 2 audit commitee independence has an insignificant effect on profitability. In model 1 audit commitee meetings have an insignificant effect on profitability. In model 2, audit committee meetings have a negative and significant effect on profitability. In model 1, board size has a negative and significant effect on profitability. Model 2, board size has a positive and significant effect on profitability. In model 1 ownership concentration has an insignificant effect on profitability. In model 2 ownership concentration has a positive and significant effect on profitability. In model 2, audit committee size moderated by ownership concentration has an insignificant effect on profitability. In model 2 audit committee independence which is moderated by ownership concentration has an insignificant effect on profitability. In model 2 audit committee meetings moderated by ownership concentration have a positive and significant effect on profitability. In model 2 board size which is moderated by ownership concentration has a negative and significant effect on profitability. bank size has a positive and significant effect on profitability. And the leverage variable has a negative and significant effect on profitability.